2014
DOI: 10.11648/j.ajss.20140201.12
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Consumption Prior to, and during, a Mountain Marathon

Abstract: Participation in ultra-endurance events such as mountain marathons is increasing, yet analysis of the nutritional intake and requirements of this group of athletes have received relatively little attention. This field study examined athletes' food intake prior to, and during a mountain marathon event to assess compliance with recommendations and to identify associations with performance. Nineteen male athletes competing in the Longmynd Hike (LH) completed a 7-day food diary in the week prior to the event and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…A study by Mahon et al [49] on mountain ultramarathon runners found that despite over 65% of athletes reporting that they intended to increase their CHO intake in the week prior to the event, no participants came close to their CHO-loading recommendations of 10–12 g/kg/d in the 48 h leading up to the event. This demonstrates that although a high carbohydrate intake is well known to benefit long duration endurance performance, athletes often fail to reach daily CHO targets needed to maximize glycogen storage due to the difficulty in practical application.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Mahon et al [49] on mountain ultramarathon runners found that despite over 65% of athletes reporting that they intended to increase their CHO intake in the week prior to the event, no participants came close to their CHO-loading recommendations of 10–12 g/kg/d in the 48 h leading up to the event. This demonstrates that although a high carbohydrate intake is well known to benefit long duration endurance performance, athletes often fail to reach daily CHO targets needed to maximize glycogen storage due to the difficulty in practical application.…”
Section: Reviewmentioning
confidence: 99%
“…In a study on mountain ultramarathon runners, Mahon et al [49] found that those consuming suboptimal amounts of CHO had higher levels of blood β-ketones post-event and that these post-blood β-ketone levels were negatively associated with performance. This further supports the need for CHO intake during prolonged events, given that ketones are an indicator of fat metabolism, particularly if an objective is to complete the event in minimal time.…”
Section: Reviewmentioning
confidence: 99%
“…This is an important consideration for athletes competing in MSUs, as it seems that relying on subjective feelings of hunger to guide EI is not an effective strategy and will likely result in large energy deficit and low EA, which may compromise performance. Indeed, a higher calorie intake has explained over 60% variation in performance during an ultramarathon (Mahon et al, 2014). Therefore, athletes unaccustomed to a MSU event are likely to benefit from a strategic diet plan to minimize energy deficit and maximize performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an inadequate energy intake, resulting in a large energy deficit, could compromise performance (Mahon, Hackett, Stott, George, & Davies, 2014). Previous research indicates that it is possible to maintain energy balance over the course of a five-day (960 km) ultramarathon (Rontoyannis et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The violation of water-electrolytic balance accompanies a number of pathological conditions and causes alteration of the organs and systems of an organism [7,10,21]. WHO informs that about 1.5 million people die annually from dehydration in the world [15,18]. Understanding the vital role of water in a human body is the basis for comprehending the development mechanisms of pathological conditions [1,2,8,25].…”
Section: Introductionmentioning
confidence: 99%